The Roles Of Factors Determining The Relation Between Budgetary Partisipation And Budgetary Slack (A Study Case in Universitas Negeri Manado) - Johny Manaroinsong; Mareyke Greety Velma Sumual (Journal of International Conference Proceedings (JICP), 2019)
This research aims at analyzing the relation between budgetary partisipation and budgetary slack as well as assessing the roles of organizational culture and group cohesiveness which are assumed to increase the impactt on relation between budgetary partisipation and budgetary slack. Further, this research examines: 1) the influence of budgetary partisipation on budgetary slack; 2) the impactt of organizational culture as the moderating variable on the relation between budgetary partisipation and budgetary slack; 3) the impact of group cohesiveness as the moderating variable on the relation between budgetary partisipation and budgetary slack. The research applies empirical and structured model by employing explanatory survey method which enables the researcher to test hypothesis by investigating the interaction among research variables. The research population is the members of institutional units in Universitas Negeri Manado consisting of 8 faculties/graduate programs/institutions. The respondents are 72 university staffs who have held certain positions for at least one year. Due to the limited number of research population, all research Samples become research target. Thus, this is a population research. The findings of this research are; 1) budgetary Partisipation has a positive influence on budgetary slack; 2) organizational culture as the moderating variable has a siginificant effect on the relation between budgetary partisipation and budgetary slack; 3) Group cohesiveness organizational culture as the moderating variable has a siginificant effect on the relation between budgetary partisipation and budgetary slack.